STUDY OF NANOTUBE GROWTH IN THE INSTALLATION WITH FERROCENE VAPOR GENERATOR - Nesterenkov, P. A.; Nesterenkov, A. G. (Recent Contributions to Physics, 2018)
Obtain nanotubes by thermal decomposition of ferrocene used as the source of catalyst and carbon with the introduction of additional carbon from the consumable graphite anode arc was investigated. Ferrocene was evaporated in a ring oscillator and injected along the perimeter of the substrate at high temperatures of the reactor in the mode of closed electrode power source and mode of electric arc combustion. In the second case provides the optimum level of temperature for the process and intensify the process of decomposition of С5H5 ligand catalyst that led to the mass production of multiwalled nanotubes in the gas phase.